문화제의 명성이 농산물브랜드 재구매에 미치는 영향: 2010 세계대백제전을 중심으로 - 권기대 (한국농촌경제연구원, 2012)
This study is an exploratory case study analyzing the relationship between cultural reputation (i.e., reputation of a local cultural festival) and intentions to repurchase local agricultural brands (i.e., the effect of a Baekje cultural festival's image, visitors' satisfaction level, and the festival's reputation on visitors' intentions to repurchase Goodtrae brand agricultural products). We collected statistically usable data from 268 questionnaire respondents who live in Chungcheong provinces and analyzed them with SPSS 18.0. Analysis results revealed that, first, brand image and visitor's satisfaction of 2010 Great Baekje World Festival had influence on the reputation of the cultural festival. Second, the survey found that reputation has influence on the visitors' intentions to repurchase Goodtrae brand agricultural products.
Keywords: 축제 브랜드 이미지; 방문객 만족; 명성; 브랜드 재구매 의향; 굿뜨래; festival brand image; visitor satisfaction; reputation; brand repurchase intentions; Goodtrae